The Influence of Physical Education Management on the Psychological Quality of College Students - Min Zhao; Tianyu Zhang, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
The research conducted to check influence of physical education management on the psychological quality of college students. To get this objective, total of 90 students from 2020 and 2021 general courses at a certain city's University of Political Science and Law were selected as the research subjects. We have developed an expert questionnaire on the relevant content of this topic, and conducted interviews and questionnaire surveys with experts and scholars from 7000 provinces and cities across the country. There are two natural teaching classes for students in the 2020 and 2021 general courses, respectively, randomly divide the samples into an experimental group and a control group, with 45 participants in each class. The technical evaluation test adopts a "single blind method", and the main participant independently scores according to a unified standard without understanding the other groups of the test subjects. The testing standards are based on the teaching standards of the corresponding teaching stage of the experimental group. Using literature review, classroom teaching, discussion, and logical reasoning methods for research. (1) The teaching content should adapt to social needs, meet students' individual development, value creativity, and master and apply knowledge, technology, and methods. Update the content as needed. (2) The teaching forms are diverse and in line with the physical and mental characteristics of students, emphasizing the combination of psychological development laws and intellectual and non-intellectual factors. (3) Teaching organizations should use flexible grouping based on students' mastery of knowledge and psychological characteristics, and pay attention to individual differences and level differences. Flexible and diverse organizational forms create a relaxed, lively, and happy learning atmosphere. (4) The teaching method mainly focuses on inspiring and inducing lectures, emphasizing the mentality and feelings during the learning process, and cultivating practical and creative abilities. In short, through physical education teaching, students can fully enjoy the fun brought by sports, achieve healthy physical and mental development, truly understand the significance of fitness, and prepare for future adaptation to the needs of society.